Tungsten phosphide (WP) nanoparticles with tunable crystallinity, W vacancies, and electronic structures for hydrogen production. (10th November 2019) - Zhang, Xiangyong; Guo, Ting; Liu, Tianying; Lv, Kangyan; Wu, Zhuangzhi; Wang, Dezhi
Abstract: Tungsten phosphide (WP) has attracted increasing attention in hydrogen evolution reaction (HER) due to its unique catalytic and electronic properties. However, its high preparation temperature often leads to particle excess growth and coarsening. Although tremendous efforts have been made to enlarge the surface areas and reduce particle size, the required high preparation temperature still limits its development. Herein, a facile self-exothermic reduction strategy under an extremely low temperature (300 °C) is proposed to prepare the ultra-fine WP nanoparticles with rich W vacancies. Remarkably, as revealed by XRD, TEM, ICP-OES and XPS analysis, the crystallinity, W vacancies and electron distribution of WP can be well controlled. The W vacancies can activate the neighboring P atoms and the bridge sites as active sites for HER, but also will change the electron distribution, which in turn deteriorates the conductivity of WP. By means of controllable W vacancies, the optimized low crystalline WP catalyst with a moderate number of W vacancies can be obtained, exhibiting a superior HER activity in acidic solution with a small Tafel slope (52 mV dec −1 ), which are smaller than most of WP-based catalysts and among the best records. Furthermore, this work will open a new horizon for both preparation and HER performance improvement of other transition metal phosphides. Graphical abstract: Image 1 Highlights: WP was successfully synthesized under an extremely low temperature of 300 °C. The crystallinity, W vacancies and electron distribution of WP were regulated. The balance between rich active sites and the good conductivity of WP is achieved. The optimal LC-WP exhibited a superior HER performance and excellent stability.